Ca2+ sensitivity of contractile system and Ca2+ release from sarcoplasmic reticulum in skinned myocardium from rats with pressure overload LV hypertrophy and heart failure. - Huang Yan; Li Yun-xia (Acta Pharmacologica Sinica, 2016)
AIM: To explore the possible subcellular mechanisms underlying the decreased contractility of myocardium in left ventricle failured hearts caused by pressure overload. METHODS: Left ventricle pressure overload hypertrophy (LVH) and congestive heart failure (CHF) models were created in rats by ascending aortic banding. Left ventricle trabeculae skinned fibers were prepared by treatment with saponin 500 or 50 mg.L-1. Relative Ca(2+)-activated tensions (T6.0% and T5.6%) of saponin (500 mg.L-1)-skinned fibers were taken as the indices of Ca2+ sensitivity of contractile protein, caffeine-induced contracture of saponin 50 mg.L-1-skinned fibers was an index of Ca2+ release from sarcoplasmic reticulum (SR). RESULTS: 1) There was no significant difference in relative Ca2+ activated tensions among CHF, LVH, and Sham-operated group in basic situation (P > 0.05). After treatment with caffeine 10 mmol.L-1, the increase in value of delta T% were significantly higher in LVH and CHF compared with that in Sham-operated control (P < 0.01). 2) The amplitudes of caffeine (5 and 10 mmol.L-1)-induced contracture were (0.66 +/- 0.14) and (1.20 +/- 0.27) g/mm2 in control group, 19.8% and 25.8% lower in LVH (P < 0.05), 78.8% and 80.9% much more lower in CHF (P < 0.01). CONCLUSION: Decreased SR Ca2+ release was the main factor responsible for depressed contractility in failured myocardium while the Ca2+ sensitivity of contractile protein might not be involved.